3D modelling the invisible using ground penetrating radar - Agrafiotis, Panagiotis; Lampropoulos, K.; Georgopoulos, Andreas; Moropoulou, A. (My University, 2017)
An interdisciplinary team from the National Technical University of Athens is performing the restoration of the Holy Aedicule, which covers the Tomb of Christ within the Church of the Holy Sepulchre in Jerusalem. The first important task was to geometrically document the monument for the production of the necessary base material on which the structural and material prospection studies would be based. One task of this action was to assess the structural behavior of this edifice in order to support subsequent works. It was imperative that the internal composition of the construction be documented as reliably as possible. To this end several data acquisition techniques were employed, among them ground penetrating radar. Interpretation of these measurements revealed the position of the rock, remnants of the initial cave of the bunal of Christ. This paper reports on the methodology employed to construct the 3D model of the rock and introduce it into the 3D model of the whole building, thus enhancing the information about the structure. The conversion of the radargrams to horizontal sections of the rock is explained and the construction of the 3D model and its insertion into the 3D model of the Holy Aedicule is descnbed.
Keywords: 3D modelling; Ground penetrating radar (GPR); Holy aedicule